Pengaruh Konseling Gizi Terhadap Pengetahuan dan Pola Asuh Ibu Balita Gizi Kurang di Wilayah Kerja Puskesmas Rapak Mahang Tenggarong - Hesti Rahayu; Iriyani K; Dina Lusiana S. (Faletehan Health Journal, 2018)
Nutritional deficiency in children under five years old can affect their brain development. At the national level, the percentage of nutritional deficiency-malnutrition cases in 2013 reached 19.3 %. This research aimed to find out the effect of nutrition counseling on the knowledge and parenting of the mothers of with nutritional deficiency in the operational area of Puskesmas Rapak Mahang. The method used in this research was quasi experiment with nonequivalent control group design. In this research used 30 respondents for experiment and control group. The method for determined respondent was nonprobability sampling with accidental sampling, The instrument that used in this research was questionnaire. The data were analyzed by using statistical analysis of Wilcoxon at the significance level of 0.05. The result of statistical analysis showed that there was an effect of nutrition counseling on the knowledge about nutrition (p value = 0.001) and there was an effect of nutrition counseling on the parenting of the mothers in the experimental group (p value = 0.001). It is suggested that nutrition counseling be given at Posyandu (Integrated Service Post) so that the mothers of balita who do not visit the Puskesmas will get nutrition counseling.